Do running speed and shoe cushioning influence impact loading and tibial shock in basketball players? - Wing-Kai Lam; Jacobus Liebenberg; Jeonghyun Woo; Sang-Kyoon Park; Suk-Hoon Yoon; Roy Tsz-Hei Cheung; Jiseon Ryu (PeerJ, 2018)
Background Tibial stress fracture (TSF) is a common injury in basketball players. This condition has been associated with high tibial shock and impact loading, which can be affected by running speed, footwear condition, and footstrike pattern. However, these relationships were established in runners but not in basketball players, with very little research done on impact loading and speed. Hence, this study compared tibial shock, impact loading, and foot strike pattern in basketball players running at different speeds with different shoe cushioning properties/performances. Methods Eighteen male collegiate basketball players performed straight running trials with different shoe cushioning (regular-, better-, and best-cushioning) and running speed conditions (3.0 m/s vs. 6.0 m/s) on a flat instrumented runway. Tri-axial accelerometer, force plate and motion capture system were used to determine tibial accelerations, vertical ground reaction forces and footstrike patterns in each condition, respectively. Comfort perception was indicated on a 150 mm Visual Analogue Scale. A 2 (speed) × 3 (footwear) repeated measures ANOVA was used to examine the main effects of shoe cushioning and running speeds. Results Greater tibial shock (P < 0.001; η2 = 0.80) and impact loading (P < 0.001; η2 = 0.73–0.87) were experienced at faster running speeds. Interestingly, shoes with regular-cushioning or best-cushioning resulted in greater tibial shock (P = 0.03; η2 = 0.39) and impact loading (P = 0.03; η2 = 0.38–0.68) than shoes with better-cushioning. Basketball players continued using a rearfoot strike during running, regardless of running speed and footwear cushioning conditions (P > 0.14; η2 = 0.13). Discussion There may be an optimal band of shoe cushioning for better protection against TSF. These findings may provide insights to formulate rehabilitation protocols for basketball players who are recovering from TSF.